Restraining The Information Dissemination On The Internet - Gábriš, Tomáš; Kovár, Ladislav (Communication Today, 2025)
Restriction of information dissemination on the Internet has various facets and follows various goals. In general, in democracies, it is only allowed upon meeting the standards of balanced rights, freedoms and overriding interests – freedom of expression/speech on the one hand and the protection of rights and freedoms of other human beings or public interest on the other. Proportionality has to be always taken into account in order not to disproportionately affect (limit) fundamental rights. Besides governmental restrictions, private restriction of information dissemination is also present, performed by religious groups, both public and private mass media and private individuals and corporations. Two types of restrictions – technical and non-technical can be discerned. From another point of view, self-censorship, or internal restriction can also be distinguished as opposed to external restrictions. Finally, preventive and repressive restrictions are being applied.